Influence of Secondary Phases in Kesterite-Cu2ZnSnS4 Absorber Material Based on the First Principles Calculation - Wujisiguleng Bao; Masaya Ichimura (International Journal of Photoenergy)
The influence of secondary phases of ZnS and Cu2SnS3 (CTS) in Cu2ZnSnS4 (CZTS) absorber material has been studied by calculating the band offsets at the CTS/CZTS/ZnS multilayer heterojunction interfaces on the basis of the first principles band structure calculation. The ZnS/CZTS heterointerface is of type I and since ZnS has a larger band gap than that of CZTS, the ZnS phase in CZTS is predicted to be resistive barriers for carriers. The CTS/CZTS heterointerface is of type I; that is, the band gap of CTS is located within the band gap of CZTS. Therefore, the CTS phase will act as a recombination site in CZTS.